Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.4039/ent122921-9
|View full text |Cite
|
Sign up to set email alerts
|

INTRODUCTION, PERMANENT ESTABLISHMENT, AND DISPERSAL IN EASTERN CANADA OF OLESICAMPE GENICULATAE QUEDNAU AND LIM (HYMENOPTERA: ICHNEUMONIDAE), AN IMPORTANT BIOLOGICAL CONTROL AGENT OF THE MOUNTAIN ASH SAWFLY, PRISTIPHORA GENICULATA (HARTIG) (HYMENOPTERA: TENTHREDINIDAE)

Abstract: From 1976 to 1978, 1300 mated females of Olesicampe geniculatae Quednau and Lim were released near Quebec City during a severe infestation of the mountain ash sawfly, Pristiphora geniculata (Hartig). Both cage and open releases were made. The interactions among the mountain ash sawfly, the imported primary parasite O. geniculatae, and the indigenous hyperparasite Mesochorus globulator (Thunb.), and the effect of O. geniculatae on the host population during and after the establishment phase, are reported. In 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…No earlyseason species were found at the surrounding sites either, but this may be due to the effect of this large horse-chestnut forest being observed over greater distances. Parasitoids are known to spread quickly and far if necessary (Quednau 1990), and the billions of parasitoids (or predators) emerging in spring from dead horse-chestnut leaves may fly long distances to find suitable hosts. Further studies on C. ohridella and native leaf miners should include an assessment of the spatial scale of the effects of apparent competition on natural leaf miner communities (Morris et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…No earlyseason species were found at the surrounding sites either, but this may be due to the effect of this large horse-chestnut forest being observed over greater distances. Parasitoids are known to spread quickly and far if necessary (Quednau 1990), and the billions of parasitoids (or predators) emerging in spring from dead horse-chestnut leaves may fly long distances to find suitable hosts. Further studies on C. ohridella and native leaf miners should include an assessment of the spatial scale of the effects of apparent competition on natural leaf miner communities (Morris et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Beirne (1967) suggested that thèse catégories were appropriate and should be considered in this exact séquence in ail integrated pest management programs. Those attributes that contribute to a good natural enemy hâve been outlined by several authors (Huffakerand Kennett 1969;Luck 1990;Mackauer 1976;Quednau 1990). …”
Section: Approaches To Implemeimting Biological Controlmentioning
confidence: 94%
“…The success rate of thèse introductions has been the source of considérable controversy, however, it is generally agreed that of thèse attempts, 34-40% hâve become established (Hall and Ehler 1979;Waage and Greathead 1988) and approximately 16% are considered to be successful in terms of control (Myers et al 1989 Reeks and Cameron 1971) and for individual cases on the winter moth (Caltagirone 1981;Murdoch et al 1985;Roland 1988), larch sawfly (Graham 1931), and European pine shoot moth (Juillet 1960;Miller 1967;Pointing and Green 1962). The cost:benefit relationship for the program against the European pine shoot moth was estimated at $300 000:>$6 million (1:75) and that for the winter moth at $160 000:>$12 million (1:20 (Quednau 1990), parasitism levels of the sawfly were 6-94% with no major infestations recorded in Québec during the last seven years. Reeks and Cameron 1971).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations